Weights of hair between Arabic and others (Journal of the College of Basic Education, 2023)
Praise be to God, and prayers and peace be upon the Messenger of God, his family, his companions, and those who followed him, and after.Meter is an important characteristic of poetry, as it is the most important thing that distinguishes poetry from prose.And the Arabs, in their definition of poetry, said that it is “rhymed, measured words that indicate meaning.” They made meter A condition of building the poem.There are many languages ​​in the world with the multiplicity of peoples in what they speak, and each language has its own system.It also has its own poetry, so the meter varied with the diversity of languages, for Arabic has a different meter or meter.